Enhanced optical absorption via cation doping hybrid lead iodine perovskites - Zhen-Kun Tang (Nature Portfolio, 2017)
Abstract The suitable band structure is vital for perovskite solar cells, which greatly affect the high photoelectric conversion efficiency. Cation substitution is an effective approach to tune the electric structure, carrier concentration, and optical absorption of hybrid lead iodine perovskites. In this work, the electronic structures and optical properties of cation (Bi, Sn, and TI) doped tetragonal formamidinium lead iodine CH(NH2)2PbI3 (FAPbI3) are studied by first-principles calculations. For comparison, the cation-doped tetragonal methylammonium lead iodine CH3NH3PbI3 (MAPbI3) are also considered. The calculated formation energies reveal that the Sn atom is easier to dope in the tetragonal MAPbI3/FAPbI3 structure due to the small formation energy of about 0.3 eV. Besides, the band gap of Sn-doped MAPbI3/FAPbI3 is 1.30/1.40 eV, which is considerably smaller than the un-doped tetragonal MAPbI3/FAPbI3. More importantly, compare with the un-doped tetragonal MAPbI3/FAPbI3, the Sn-doped MAPbI3 and FAPbI3 have the larger optical absorption coefficient and theoretical maximum efficiency, especially for Sn-doped FAPbI3. The lower formation energy, suitable band gap and outstanding optical absorption of the Sn-doped FAPbI3 make it promising candidates for high-efficient perovskite cells.